Understanding Halal Awareness in the Digital Age: A Millennial Perspective - Muhammad Syarofi; Muhammad Lathoif Ghozali; Majdy Kasheem (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Lack of education and socialization about halal in the digital era creates a gap in understanding and awareness of halal by the millennial generation, this has an impact on the low concern of this generation towards the importance of consuming halal products and poses a risk in choosing products that are in accordance with halal principles. Without adequate education, the millennial generation tends to pay less attention to halal and tayyib aspects, which can affect their health and quality of life in accordance with Islamic values.The purpose of this study is to understand how halal awareness is formed among the millennial generation in the digital era.This research uses the method systematic literature review comprehensive understanding of halal awareness among millennials in the context of the digital era, involving the search and analysis of relevant reference sources, such as books, national journals, and international journals, related to the research topic. The results of this study indicate that the level of halal awareness among Indonesian Muslim millennials influenced by various factors, including religious beliefs, media exposure, family environment, and motivations of actors in the halal product production chain still needs to be improved. Although there is a potential for a decline in the growth of halal awareness, the lack of consistent education and policy support is the main challenge.